2011
DOI: 10.1007/s12284-011-9065-z
|View full text |Cite
|
Sign up to set email alerts
|

Rice Genotypes with SUB1 QTL Differ in Submergence Tolerance, Elongation Ability during Submergence and Re-generation Growth at Re-emergence

Abstract: Submergence tolerance is an important trait where short term flash flooding damages rice. Tolerant landraces that withstand submergence for 1–2 weeks were identified. Due to the heterogeneity in flood-prone ecosystem many different types of traditional rice cultivars are being grown by the farmers. The local landraces adapted to extremes in water availability could be the sources of genetic variation are to be used to improve the adaptability of rice to excess water stress. Greater genotypic variability was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 32 publications
4
61
0
Order By: Relevance
“…The stagnant sub-1 rice may be valuable from the middle zone to the flood limit field, in years when maximum water depth was shallower but flash flood occurs. Cultivars would be needed which possess SUB1 and at the same time show some degrees of elongation due to flooding in order better to cope with the various deep water environments, and such types of germplasms lines were reported (Sarkar and Bhattacharjee 2011). Appropriate crop management was also important to cope with the dry-spell and assist plant elongation during flooding from September, as discussed by others (Bouman et al 2007;Puckridge et al 1989).…”
Section: Rice Damage Statisticsmentioning
confidence: 98%
“…The stagnant sub-1 rice may be valuable from the middle zone to the flood limit field, in years when maximum water depth was shallower but flash flood occurs. Cultivars would be needed which possess SUB1 and at the same time show some degrees of elongation due to flooding in order better to cope with the various deep water environments, and such types of germplasms lines were reported (Sarkar and Bhattacharjee 2011). Appropriate crop management was also important to cope with the dry-spell and assist plant elongation during flooding from September, as discussed by others (Bouman et al 2007;Puckridge et al 1989).…”
Section: Rice Damage Statisticsmentioning
confidence: 98%
“…Analysis of flooding pattern in rainfed lowland of Southeast Asia reveals that about 20 million ha comes under medium-deep to deep and very deep ecology based on water stagnation. Here, the ideal response to flooding is submergence tolerance (survival under water) together with some elongating ability [4,30,32]. Is the extent of injury caused by complete submergence is alike both in tolerant and elongating type rice cultivars?…”
Section: Introductionmentioning
confidence: 99%
“…Results of PCR revealed that ART5 which is a closely linked marker in the promoter region of SUB1C a transcription-factor gene [3] showed bands in some of the genotypes while the presence of this marker was nullified in all the rest of the genotypes used in this study. …”
Section: ) Molecular Screeningmentioning
confidence: 63%
“…In Pakistan, approximately 70% rice farms are prone to seasonal flooding. Rice crop may be the only crop which can effectively be grown in flood prone ecosystems [3]. These floods are sometimes so damaging that rice farmers in some parts of the country lose their entire rice crop.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation